2019
DOI: 10.1109/tie.2019.2891453
|View full text |Cite
|
Sign up to set email alerts
|

A PCA and Two-Stage Bayesian Sensor Fusion Approach for Diagnosing Electrical and Mechanical Faults in Induction Motors

Abstract: Induction motors are widely used in industrial plants for critical operations. Stator faults, bearing faults or rotor faults can lead to unplanned downtime with associated cost and safety implications. Different sensors may be used to monitor the health state of induction motors with each sensor typically being better suited to diagnosing different faults. Condition monitoring approaches which fuse data from multiple sensors have the potential to diagnose a greater number of faults. A sensor fusion approach ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 30 publications
0
49
0
1
Order By: Relevance
“…It was observed that this proposed combined approach effectively and adaptively identified inner ball faults. Stief et al [33] proposed a sensor fusion approach to diagnose both electrical and mechanical faults in induction motors based on the combination of a two-stage Bayesian method and PCA. Caggiano [34] also proposed an advanced feature extraction methodology based on PCA.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that this proposed combined approach effectively and adaptively identified inner ball faults. Stief et al [33] proposed a sensor fusion approach to diagnose both electrical and mechanical faults in induction motors based on the combination of a two-stage Bayesian method and PCA. Caggiano [34] also proposed an advanced feature extraction methodology based on PCA.…”
Section: Introductionmentioning
confidence: 99%
“…The presented solutions, methods, and approaches can be improved and used in the future. Moreover, mechanical engineering is essential for fault diagnosis of machines [10][11][12][13][14][15][16][17][18][19][20][21][22] and the analysis of temperature [23][24][25]. The mechanical properties of materials are also investigated in the literature [26][27][28].…”
Section: The Contentmentioning
confidence: 99%
“…Although the wired method involves direct coupling, recent developments in wireless communication technology have enabled diagnosis without direct coupling. Furthermore, many research studies have been conducted based on the aforementioned developments [8][9][10]. Typically, amplitudes of frequencies ratio 50 s frequency coefficient (MSAF-RATIO-50-SFC), MSAF-RATIO-50-SFC-EXPANDED, MSAF-RATIO-24-MULTIEXPANDED-FILTER-8, and the shortened method of frequencies selection (SMoFS-15) are normally used, but the analysis is somewhat complicated [11,12].…”
Section: Introductionmentioning
confidence: 99%